2021
DOI: 10.1186/s13578-021-00670-w
|View full text |Cite
|
Sign up to set email alerts
|

Axon regeneration after optic nerve injury in rats can be improved via PirB knockdown in the retina

Abstract: Background In the central nervous system (CNS), three types of myelin-associated inhibitors (MAIs) exert major inhibitory effects on nerve regeneration: Nogo-A, myelin-associated glycoprotein (MAG), and oligodendrocyte-myelin glycoprotein (OMgp). MAIs have two co-receptors, Nogo receptor (NgR) and paired immunoglobulin-like receptor B (PirB). Existing studies confirm that inhibiting NgR only exerted a modest disinhibitory effect in CNS. However, the inhibitory effects of PirB on nerve regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It has been shown that POSH formed an inhibitory complex by binding to F-actin-binding protein (Shroom3), which activated the POSH/Shroom3/ROCK signaling pathway, leading to a decrease in Myosin II expression and inhibition of axonal growth (111,112). The study confirmed that the knockdown of Pir B caused more axon regeneration than the knockdown of NgR1, suggesting that Pir B plays a more important role in myelin inhibition (113). By antagonizing the action of Nogo-A and Pir B, it could inhibit POSH expression and suppress the activity of downstream molecules Shroom3/ROCK/Rho A, which effectively reverses the inhibition of its axonal growth (111,114,115).…”
Section: Nogo-amentioning
confidence: 62%
“…It has been shown that POSH formed an inhibitory complex by binding to F-actin-binding protein (Shroom3), which activated the POSH/Shroom3/ROCK signaling pathway, leading to a decrease in Myosin II expression and inhibition of axonal growth (111,112). The study confirmed that the knockdown of Pir B caused more axon regeneration than the knockdown of NgR1, suggesting that Pir B plays a more important role in myelin inhibition (113). By antagonizing the action of Nogo-A and Pir B, it could inhibit POSH expression and suppress the activity of downstream molecules Shroom3/ROCK/Rho A, which effectively reverses the inhibition of its axonal growth (111,114,115).…”
Section: Nogo-amentioning
confidence: 62%
“…To demonstrate the role of the ACC in neuropathic pain and comorbidity, we first wanted to verify the anatomical connection between the ACC and the spinal cord. Cholera toxin subunit B (CTB), taken up by axon terminals and retrogradely transported to the soma, is currently the most widely used retrograde tracer ( Yang M. et al, 2021 ). We microinjected CTB-555(250 nl, green) into the contralateral ACC and CTB-488(250 nl, red) into the ipsilateral spinal dorsal horn ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…72,73 However, even using this genome-wide loss-of-function methodology and other recently developed technologies such as single-cell RNA sequencing and transcription factor screens, researchers have not speci cally isolated regenerated cells from nonregenerated cells. [73][74][75] Unique genes and processes are involved in adult RGC axon regeneration Few studies have thoroughly investigated the role of DNA methylation in axon regeneration, particularly in relation to neuronal growth competence. 19,33,36,46,76 Recent studies have focused on transcriptional alterations associated with neuronal injury.…”
Section: Discussionmentioning
confidence: 99%